2018
DOI: 10.1016/j.ijcci.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of graphical password authentication for children

Abstract: In this paper, we explore graphical passwords as a child-friendly alternative for user authentication. We evaluate the usability of three variants of the PassTiles graphical password scheme for children, and explore the similarities and differences in performance and preferences between children and adults while using these schemes. Children were most successful at recalling passwords containing images of distinct objects. Both children and adults prefer graphical passwords to their existing schemes, but passw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…It can be configured to retrieve information from memory using recognition, free-recall or cued-recall. Assal et al [3] conducted a study to understand differences between children and adults authenticating using three PassTiles schemes. The three main variations of PassTiles used in the study are: Objects [34], Image [34], and Words [38] schemes.…”
Section: Graphical Based Authentication For Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be configured to retrieve information from memory using recognition, free-recall or cued-recall. Assal et al [3] conducted a study to understand differences between children and adults authenticating using three PassTiles schemes. The three main variations of PassTiles used in the study are: Objects [34], Image [34], and Words [38] schemes.…”
Section: Graphical Based Authentication For Childrenmentioning
confidence: 99%
“…[25] findings; they found that young children do not have good mental models privacy. Assal et al [3] recommend that when designing authentication systems for children, we need to take into consideration their cognitive abilities and skills. They propose three design recommendations for authentication system designed for children: facilitate memorization through learning and training features; adapt the interface to be age-appropriate for children; combine schemes to improve memorability (Objects and Images).…”
Section: Graphical Based Authentication For Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is vulnerable because attackers can capture the characters key in by the user and subsequently use it to login legitimately. Assal et al proposed an authentication method in 2016 [10]. During the registration procedure, a user is required to register five images from the images shown in the 8 x 6 grid cell.…”
Section: Related Workmentioning
confidence: 99%
“…Authentication can be categorised into three categories: token-based, biometric-based and knowledge-based [1]. Token-based authentication relies on what the users possess (e.g., ID card) to perform authentication, biometric-based authentication relies on users' attributes (e.g., thumbprint) to perform authentication, while knowledge-based authentication relies on what the users know (e.g., alphanumeric password) to perform authentication [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%